Sleep Quality and Nocturnal Pain in Patients of Rotator Cuff Syndrome - Tazeen Zahra, Faiza Altaf, Huma Akhtar, Somia Sabeeh Awan, Umais Ali Sher, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Shoulder pain during sleep leads to poor quality sleep. It is a common problem in patients with Rotator cuff syndrome. Rotator cuff syndrome is a condition where your rotator cuff tendons are intermittently trapped and pinched during shoulder movements Objective: To evaluate the relationship between sleep quality and nocturnal pain in patients of rotator cuff syndrome. Methods: Current study was conducted in orthopedic and physiotherapy department of Jinnah Hospital Lahore. Cross-sectional survey was used in this study. Subjects with age group 18-75 years, both genders, diagnosed with rotator cuff syndrome with positive shoulder impingement test and empty can test were included. Patients were requested to fill the comprehensive questionnaire about current medical history, shoulder pain, impact on daily life activities and quality of sleep. Patients with coexisting neck pain and radiculopathies (spleen, kidney, gallbladder) and also with other disabilities e.g., osteoarthritis, rheumatoid arthritis, back pain were excluded from current study. Thirty-six patients were enrolled and examined by using Pittsburgh Sleep Quality Index (PSQI). Data was analyzed using SPSS 20.0. Results: The results showed that sleep quality was disturbed in patients of rotator cuff syndrome with a mean Pittsburgh Sleep Quality Index score of 11.3333. The results showed that among 36 patients, 18 (50%) had moderate disturbance of sleep as calculated by PSQI scale and 11 (30.6%) had severe disturbance of sleep while 7 (19.4%) had mild disturbance of sleep due to rotator cuff syndrome. Conclusion: The current study concluded that subjective sleep disturbance connected to shoulder pain was obvious in patients with rotator cuff syndrome. Patients experienced low quality of sleep associated with rotator cuff syndrome and affected their activities of daily living causing severe pain and physical disability. Keywords: Shoulder pain, rotator cuff syndrome, Sleep quality.